PELATIHAN DAN PENDAMPINGAN SERVICE EXCELLENCES PADA GANJURAN FOOD COURT - Pramudita, Dismas Persada Dewangga; Bhimasta, Raden Agoeng; Kinanthi, Enggar Sukma; Febrian, Agy; Jonathan, Milo (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community engagement aimed to enhance service quality among culinary entrepreneurs at Ganjuran Food Court (GFC) through training and mentoring grounded in service excellence. The program consisted of six sessions: introduction to quality service, SERVQUAL dimensions, ten core service principles, customer journey mapping, service improvement strategies, and complaint handling role-plays. Delivered in a participatory and contextual format, the training was followed by field mentoring. Results showed that participants began applying more responsive and customer-oriented practices. Innovations such as QR-based ordering and service flow banners emerged as part of ongoing improvements. This initiative laid the foundation for a service-minded culture and future development through branding, digital marketing, and product diversification.